FORMATION OF PROGRAMMING COMPETENCE OF ENGINEERS IN THE DIGITAL EDUCATIONAL ENVIRONMENT - Yelena Kodirova (Web of Journals Publishing, 2026)
The purpose of this study is to develop and implement a methodology for forming programming competence among engineering students within a digital educational environment. As a tool for digitalizing the learning process, software-didactic support integrated into the discipline “Information Technologies in Technical Systems” was employed. The methodological foundation includes the principles of competence-oriented learning, the ADDIE model, as well as regulatory frameworks such as CDIO, O‘zDSt, and ACM/IEEE. Within the study, a structure of digital integration was established, encompassing all forms of educational activity: classroom-based (lectures, practical and laboratory sessions) and extracurricular. The methodology is implemented through the sequential introduction of digital components—interactive tasks, tests, flowchart and code editors, as well as feedback mechanisms. The obtained results demonstrate increased learning activity, improved quality of task performance, and the development of sustainable skills in algorithmization and programming. Assessment tools are embedded in the digital environment, ensuring transparency of monitoring and the possibility of cumulative achievement tracking. The main conclusion confirms the effectiveness of the proposed methodology, which provides systemic digital transformation of the discipline and attainment of targeted educational outcomes. The developed model can be adapted for other technical disciplines and digital platforms.
Keywords: Engineering education, competence-based approach, programming, algorithmization, digital educational environment, software-didactic support, interactive tasks, learning outcomes assessment, digital transformation, ITTS platform.